Evaluasi Sistem Informasi Human Resources Management Systems PT MMC Metal Fabrication Bekasi - Aditya Ramadhani Zulfa; Petrus Dwi Ananto Pamungkas (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
The HRMS (Human Resources Management System) Information System functions to process employee data related to the Human Resources Department. After running this HRMS Information System for several years, the leadership of PT MMC Metal Fabrication wanted to find out the extent of maturity and the shortcomings found in the HRMS Information System. To find out the extent of maturity of the HRMS Information System, an HRMS Information System Evaluation is needed. To adjust the standards in Indonesia, Information System Evaluation is made using the Index KAMI (Information Security). Index KAMI is an Information System Evaluation framework adopted from ISO 27001 that has been adjusted to the standards in Indonesia. The results of this study can provide the maturity level of the HRMS Information System along with the findings.